Middle East and North Africa Economic Developments and Prospects, 2009 : Navigating through the Global Recession - World Bank (Washington, DC, 2014)
The objective of this 2009 Middle East and North Africa (MENA) economic developments and prospects is to review the implication of the triple food-fuel-financial crisis for MENA economies. Chapter one reviews the year 2008 and the first few months of 2009. It discusses the impact of the global economic environment and MENA countries' responses to the initial impact of the food-fuel-financial crises. Chapter two reviews MENA countries' prospects for 2009 and 2010 and discusses policies that can be envisaged to mitigate the impact of the global financial crisis on the region. Finally, chapter three goes beyond the short-term concerns about the current crisis and discusses structural factors that affect MENA countries' vulnerability to shocks and their flexibility and ability to respond to future crises. The main conclusions of the report are: (a) the effect of the crisis depends on countries' exposure to affected markets and commodities as well as on their initial macroeconomic conditions and policies; and (b) in terms of impact on the real economy, the MENA region held up well in 2008, with average Gross Domestic Product (GDP) growth remaining steady while other regions experienced declining growth.